Social–emotional competencies and character are at the foundation of education regardless of technology - Elias, Maurice J. (Frontiers in Education, 2025)
Innovative technologies like AI need to be brought into education in ways that will support best pedagogical practices. Examining the history of adoption of innovations shows that their impact often is hard to predict. Future use of AI must be accompanied by clarity about the educational purposes that AI is intended to enhance. Key to ensuring that AI’s impact is positive is recognizing that AI is operator dependent, and the social–emotional and character competencies of those implementing and using AI innovations – along with the prosocial value structure of their schools, particularly around academic integrity—will determine the impact of AI. This is illustrated with examples of cyberbullying and the presence of Chromebooks in classrooms. Policy and practice recommendations are provided, centered around the prioritization of collaborative and experiential pedagogy and systematic, intentional social–emotional and character development for all children in all schools.